UNEXPECTED RESPONSE OF MT. WRANGELL VOLCANO, ALASKA, TO THE SHAKING FROM A LARGE REGIONAL EARTHQUAKE: A PUZZLE FOR INTERMEDIATE-TERM EARTHQUAKE-VOLCANOES INTERACTIONS - Sánchez, John J.; McNutt, Stephen R. (Earth Sciences Research Journal, 2004)
On November 3, 2002 three segments of the Denali fault in interior Alaska ruptured during a Mw 7.9 earthquake, offering a unique opportunity to study earthquake-volcano interactions. Out of the 24 volcanoes that are seismically monitored by the Alaska Volcano Observatory (AVO) only Mt. Wrangell, the closest volcano to the epicenter (247 km), showed a clear response to the shaking in the intermediate-term (weeks to months) time scale. The response was unexpected because it consisted of a decline by at least 50% in the volcano's seismicity rate (mostly low-frequency events) that lasted for five months. Because most well documented previous instances of short-term (minutes to days) responses of volcanic centers to the passing waves of distant earthquakes, have all been seismicity increases, the decline in seismicity at Mt. Wrangell poses a controversial puzzle. By using several independent methods to measure the seismicity rate at the volcano from before to after the main shock, and applying rigorous statistical testing, we conclude that the change in seismicity at the volcano was a real effect of the Denali earthquake. We suggest that a depressurization of the volcanic plumbing system took place either as a result of sudden decompression (static stress changes) or because of creation of new pathways resulting from the strong shaking (dynamic stresses). At present we cannot distinguish between these two possibilities.